O, S, C isotopic signatures of high-arsenic groundwater in Ngari, Xizang: Seasonal-scale drivers of arsenic release mechanisms - Lian Song; Shehong Li; Jen-How Huang; Fei He; Qiao Han; Jie Liao; Zhenjie Zhao; Ci Ren Qu Ji; Yong Shui (Acta Geochimica, 2026)

Hybrid apoptotic body decorated supramolecular hydrogel system for melanoma cancer immunoediting - Wei-Yuan Huang; Nai-Wen Liang; Li-Jen Yu; Chen-Hsiang Kuan; Chien-Wen Chang; Tsung-Chiao Wu; Yu-Tso Liao; Tzu-Wei Wang (Chemical Engineering Journal, 2025)

A non-invasive method for sexing all castes of Prorhinotermes flavus (Blattodea: Psammotermitidae) using external morphology - Wan-Jen Li; Yi-Ning Chiu; Hauchuan Liao; Hou-Feng Li (Arthropod Structure & Development, 2025)

Currents shaped the genetic structure of Tridentiger barbatus (Günther 1861) along the Chinese coast - Jiehong Wei; Min-Yun Liu; Jen-Chieh Shiao; Fan Li; Jinquan Yang; Yoshiyuki Iizuka; Bin Kang; Ruo-Shan Tseng; Huan-Jie Shao; Te-Yu Liao (Frontiers in Marine Science, 2022)
The modern coast of China is characterized by complicated hydrology, which might be a potential factor shaping genetic structure of marine organisms. Tridentiger barbatus is a widespread benthic goby in coastal China whose range expansion might depend on larval dispersal in its spawning season. We explored the genetic structure of T. barbatus and its interrelationships with coastal currents, planktonic larval duration, and Pleistocene climate fluctuations. Genealogies of Cytb , Rh , and RAG1 reveal two lineages in T. barbatus , namely the southern and northern lineages. The southern lineage is distributed through the South China Sea to the South Yellow Sea but is absent from the North Yellow Sea and Bohai Sea. The HYCOM average flow field indicates an eddy between the North and South Yellow Seas, which might cause larval retention and limit dispersal of the southern lineage into the North Yellow Sea and the Bohai Sea. The northern lineage is distributed through the South Yellow Sea to the Bohai Sea but is absent from the South China Sea and East China Sea. The distribution of the northern lineage fits the eastward deflection of the Yellow Sea Coastal Current at the boundary of the East China Sea and South Yellow Sea, which might limit southward larval dispersal of the northern lineage into the East China Sea. We also uncovered two Cytb haplotype groups within the southern lineage, namely groups A and B, whose distributions might be shaped by the northward Taiwan Strait Current. The coincidence between the genetic structure of T. barbatus and the coastal currents and eddies strongly implies significant roles of larval dispersal and current transportation in shaping the genetic structure of T. barbatus . In addition, significant isolation by distance is found in the southern lineage, which coincides with its short planktonic larval duration (20–30 days). The inference on divergence time suggests that the observed lineages and haplotype groups in T. barbatus originated in the Pleistocene glaciations. Therefore, the coastal currents, planktonic larval duration, and historical glacial isolation are proposed as important factors shaping the genetic structure of T. barbatus .

Streptococcus vulneris sp. nov., isolated from wound of patient with diabetic foot ulcer (DFU) - Jen-hao Chung; Li-Ting Wang; Yi-Sheng Chen; Yun-Shien Lee; Shih-Ting Lin; Yu-Chung Chang; Hui-Chung Wu; Yu-Jie Dai; Wei-Qi Liao; Fan-Ching Kao; Jui-hsiang Li (Archives of Microbiology, 2022)

A meta-analysis of genome-wide association studies using Japanese and Taiwanese has revealed novel loci associated with gout susceptibility - Shun-Jen Chang; Yu Toyoda; Yusuke Kawamura; Takahiro Nakamura; Masahiro Nakatochi; Akiyoshi Nakayama; Wei-Ting Liao; Seiko Shimizu; Tappei Takada; Kenji Takeuchi; Kenji Wakai; Yongyong Shi; et al. (Human Cell, 2022)

Adaptation capability of rainfall hotspots in water resilient cities using QGIS: a case study of Taichung City in Taiwan - Ming-jen Cheng; Wei-liang Sia; Feng-chi Liao; Li-shin Chang (Environmental Monitoring and Assessment, 2022)

Impact of Prolonged Tablet Computer Usage with Head Forward and Neck Flexion Posture on Pain Intensity, Cervical Joint Position Sense and Balance Control in Mechanical Neck Pain Subjects - Cheng-Chieh Lin; Siang-Hua Hua; Cheng-Li Lin; Chih-Hsiu Cheng; Jen-Chieh Liao; Cheng-Feng Lin (Journal of Medical and Biological Engineering, 2020)

Cytoplasmic aryl hydrocarbon receptor regulates glycogen synthase kinase 3 beta, accelerates vimentin degradation, and suppresses epithelial–mesenchymal transition in non-small cell lung cancer cells - Ching-Hao Li; Chen-Wei Liu; Chi-Hao Tsai; Yi-Jen Peng; Yu-Hsuan Yang; Po-Lin Liao; Chen-Chen Lee; Yu-Wen Cheng; Jaw-Jou Kang (Archives of Toxicology, 2017)

Associations of TNF-α and IL-6 polymorphisms with osteoporosis through joint effects and interactions with LEPR gene in Taiwan: Taichung Community Health Study for Elders (TCHS-E) - Cheng-Chieh Lin; Tsai-Chung Li; Chiu-Shong Liu; Chuan-Wei Yang; Chih-Hsueh Lin; Jen-Hao Hsiao; Nai-Hsin Meng; Wen-Yuan Lin; Li-Na Liao; Chia-Ing Li; Fang-Yang Wu (Molecular Biology Reports, 2016)

Cyclic GMP-dependent protein kinase II is necessary for macrophage M1 polarization and phagocytosis via toll-like receptor 2 - Wei-Ting Liao; Huey-Ling You; Changgui Li; Jan-Gowth Chang; Shun-Jen Chang; Chung-Jen Chen (Journal of Molecular Medicine, 2015)

Establishment of an Agrobacterium-mediated genetic transformation procedure for the experimental model orchid Erycina pusilla - Shu-Hong Lee; Chia-Wen Li; Chia-Hui Liau; Pao-Yi Chang; Li-Jen Liao; Choun-Sea Lin; Ming-Tsair Chan (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Phenotypic characterization of C57BL/6J mice carrying the Disc1 gene from the 129S6/SvEv strain - Liang-Wen Juan; Chun-Chieh Liao; Wen-Sung Lai; Chia-Yuan Chang; Ju-Chun Pei; Wan-Rong Wong; Chih-Min Liu; Hai-Gwo Hwu; Li-Jen Lee (Brain Structure and Function, 2014)

Baseline human papillomavirus infection, high vaginal parity, and their interaction on cervical cancer risks after a follow-up of more than 10 years - Shu-Fen Liao; Wen-Chung Lee; Hui-Chi Chen; Li-Chung Chuang; Mei-Hung Pan; Chien-Jen Chen (Cancer Causes & Control, 2012)

Differential neuronal changes in medial prefrontal cortex, basolateral amygdala and nucleus accumbens after postweaning social isolation - Yu-Chun Wang; Ue-Cheung Ho; Meng-Ching Ko; Chun-Chieh Liao; Li-Jen Lee (Brain Structure and Function, 2012)

Evidence for structural and functional changes of subplate neurons in developing rat barrel cortex - Chun-Chieh Liao; Li-Jen Lee (Brain Structure and Function, 2012)

Micropropagation of bromeliad Aechmea fasciata via floral organ segments and effects of acclimatization on plantlet growth - Ping-Lung Huang; Li-Jen Liao; Chi-Chu Tsai; Zin-Huang Liu (Plant Cell, Tissue and Organ Culture (PCTOC), 2011)

Zebrafish eggs used as bioreactors for the production of bioactive tilapia insulin-like growth factors - Shao-Yang Hu; Chia-Hsuan Liao; Yi-Pei Lin; Yen-Hsing Li; Hong-Yi Gong; Gen-Hwa Lin; Koichi Kawakami; Tzu-Hsuan Yang; Jen-Leih Wu (Transgenic Research, 2011)

Identification and phylogenetic analysis of orf virus from goats in Taiwan - Kun-Wei Chan; Jen-Wei Lin; Shu-Hwae Lee; Chih-Jung Liao; Meng-Chun Tsai; Wei-Li Hsu; Min-Liang Wong; Hung-Chang Shih (Virus Genes, 2007)

Identification and phylogenetic analysis of orf virus from goats in Taiwan - Kun-Wei Chan; Jen-Wei Lin; Shu-Hwae Lee; Chih-Jung Liao; Meng-Chun Tsai; Wei-Li Hsu; Min-Liang Wong; Hung-Chang Shih (Virus Genes, 2007)

Gene stacking in Phalaenopsis orchid enhances dual tolerance to pathogen attack - Yuan-Li Chan; Kuang-Hung Lin; Sanjaya; Li-Jen Liao; Wen-Huei Chen; Ming-Tsair Chan (Transgenic Research, 2005)